ANTI-ICE REAGENT ON THE BASIS OF DOLOMITE, NITROGEN ACID AND CARBAMIDE - Akhmedov, Mansur; Dadakhodzhaev, Abdulla; Guro, Vitaliy (International Journal of Engineering Technologies and Management Research, 2018)
For the safe operation of pavements in the cold season, especially in mountainous areas, antiicing means are required. The task was to develop the technology of their production from local raw materials. A domestic anti-icing reagent, from unbaked dolomite from Dekhkanabad deposit of Uzbekistan was offered, consisting of calcium, magnesium nitrates and carbamide. Standard chemical-analytical methods for investigating raw materials, laboratory technological methods, enlarged pilot-industrial approaches to the methods of its processing, followed by the development of technology for obtaining the required dolomite’s derivatives, as well as its implementation at JSC "Maxam-Chirchik" were used. Sulfur-hydrochloric acid’s processing of dolomite provided bischofite’s obtaining in industrial reactors. As the result, optimal conditions for obtaining anti-ice reagent were selected for its industrial production.